A prospective controlled trial comparing spontaneous closure and Epifilm® patching in traumatic tympanic membrane perforations - Sayin, Ibrahim; Kaya, Kamil Hakan; Ekizoğlu, Oğuzhan; Erdim, İbrahim; Kayhan, Fatma Tülin (European archives of oto-rhino-laryngology, 2013)
The objective was to compare the outcomes of spontaneous closure and hyaluronic acid (HA) ester patching (Epifilm ® ) in subjects with traumatic tympanic membrane (TM) perforation. This was a prospective, controlled study performed at a tertiary teaching and research hospital. During 6-month period, subjects were divided into spontaneous closure (group A) and HA ester patch-Epifilm ® (group B) group. Demographic data, presenting symptoms, closure rate, closure time and audiometric data were evaluated and compared between groups. In total, 155 subjects were evaluated. Group A consisted of 62.6 % ( n = 97) of the subjects, whereas group B consisted of 37.4 % ( n = 58) of the subjects. Group B had significantly shorter closure times when compared with group A (6.61 ± 4.59 vs. 10.60 ± 5.23 weeks, p = 0.001). When the closure time was evaluated according to perforation size both grade 1 and 2 perforations have significantly shorter closure times when compared with group A (6.33 ± 4.54 vs. 10.80 ± 5.69 weeks, for grade 1 and 6.650 ± 2.07 vs. 10.30 ± 4.32 weeks for grade 2 perforations). Closure rates were not significant between groups (85.6 % for group A and 94.8 % for group B). When the closure rate was evaluated according to perforation size no significant difference exists for grade 1, 2 and 3 perforations between groups. Both air conduction and air-bone gap were significantly improved in both groups. HA ester patch (Epifilm ® ) is a non-toxic material that can be used in traumatic tympanic membrane perforations. In this study, use of HA ester patching was resulted with earlier closure time but not resulted with higher closure rates.